Final Cut Express HD 3.5 Editing Workshop, 3rd Edition - Wolsky, Tom (Routledge, 2012)
Go beyond the mechanics of Final Cut Express HD 3.5--learn how to edit with it! More than a button-pushing manual--this workshop give you firsthand experience with the art and technique of editing. You develop a working knowledge of this powerful editing application with eleven tutorials that cover each and every essential, including: * setting up your system and understanding the interface * getting your material into FCE and organizing it * slicing, dicing, and organizing clips * editing to build and trim a sequence of shots * adding transitions * using sound to refine your edit * titling with FCE and Photoshop * animating images to create engaging scenes * adding special effects filters * compositing to enhance your projects * outputting your material The companion DVD contains a video introduction to FCE that is especially designed for iMovie users. It compares and contrasts the two applications to ease the transition. The DVD-ROM portion contains project media, demo software, and free plug-ins for your use.